INSTAGRAM SEBAGAI MEDIA EDUKASI PENINGKATAN PENGETAHUAN KESEHATAN GIGI DAN MULUT - Ratna Sari Dyah; Lies Elina (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2021)
Knowledge of how to maintain proper dental health will greatly affect the incidence of dental caries, brushing and rinsing teeth - gargling is one of the behaviors to maintain oral hygiene. behavior based on correct knowledge will last longer than behavior that is not based on knowledge, an effort to increase knowledge is through health education. Online media is one of the educational media to increase knowledge of dental and oral health. The type of research in this study is a comparative comparative analysis or